2021
DOI: 10.1177/23998083211041122
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a multilevel approach with spatial effects to model housing price in San José, Costa Rica

Abstract: A multilevel model of the housing market for San José Metropolitan Region (Costa Rica) was developed, including spatial effects. The model is used to explore two main questions: the extent to which contextual (of the surroundings) and compositional (of the property itself) effects explain variation of housing prices and how does the relation between price and key covariates change with the introduction of multilevel effects. Hierarchical relations (lower level units nested into higher level) were modeled by sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The location of available real estate for sale is distinctly and systematically determined by geographic factors, as should be expected from such a complex setting. Future work on the point pattern analysis of real estate markets in San José could aim to find spatio-temporal patterns (and in particular, given the collected data is for 2020 and 2021, any short run variations related to the COVID-19 pandemic); in addition, previous hedonic price models of the region (Pérez-Molina 2022) would benefit from a critical reappraisal and the consideration of preferential sampling bias, along the lines of Paci et al (2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location of available real estate for sale is distinctly and systematically determined by geographic factors, as should be expected from such a complex setting. Future work on the point pattern analysis of real estate markets in San José could aim to find spatio-temporal patterns (and in particular, given the collected data is for 2020 and 2021, any short run variations related to the COVID-19 pandemic); in addition, previous hedonic price models of the region (Pérez-Molina 2022) would benefit from a critical reappraisal and the consideration of preferential sampling bias, along the lines of Paci et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…The determinants of the real estate listings point process were assumed to be similar to those of property prices. Previous studies (Pérez-Molina 2022) and theoretical developments (Koomen and Stillwell 2007) have explored the role of these determinants. Five basic patterns were selected: slope, as flatter areas are more desirable than steeper locations; elevation, because relatively higher elevations correspond to the less attractive periphery of the region; Euclidean distance from the CBD and from the nearest municipal center, as main and secondary urban centralities (Euclidean distance was chosen to reduce endogeneity introduced by the local network); Euclidean distance from main roads, being close to which represents especially good accessibility.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Table (2) above summarized the results of the relative efficiencies. The table indicates that the submodel estimator β1 SM dominates all other estimators followed by the pretest estimator β1 PTL .…”
Section: Plos Onementioning
confidence: 99%
“…For example, but not limited to, Shen X. et.al [ 1 ] proposed CA model to analyze the heterogenous genetic effects among individuals which is considered as a random effect in their model. Pérez-Molina [ 2 ] modeled hierarchical relationships using multilevel models with random intercepts and a CA component to account for spatial effects. He demonstrated that such models are significantly improve housing price modeling.…”
Section: Introductionmentioning
confidence: 99%
“…A hierarchical-spatial approach is proposed in [63] by combining spatial econometrics with a two-level approach for apartment price prediction: the first level relates to the individual apartment characteristics, and the second level includes local neighborhood characteristics. Similarly, a multilevel linear regression model is implemented in [78]; however, a conditional autoregressive term is added instead of the general spatial model that forms the basis of the multilevel model used in [63].…”
Section: Spatial Econometricsmentioning
confidence: 99%